Recent advancements in bio-based dielectric and piezoelectric polymers and their biomedical applications - Yadegari, Ali; Akbarzadeh, Mahsa; Kargaran, Farshad; Mirzaee, Ramin; Salahshoori, Iman; Nobre, Marcos A. L. [UNESP]; Khonakdar, Hossein Ali (Royal Society of Chemistry (RSC), 2024)
The advent of polymer-based dielectrics marked a significant breakthrough in dielectric materials. However, despite their many advantages, they pose serious environmental threats. Therefore, in recent years, there has been growing interest in bio-based polymers as a sustainable alternative to traditional petroleum-based polymers. Their renewable nature and reduced environmental impact can fulfil the rising demand for eco-friendly substitutes. Beyond their ecological benefits, bio-based polymers also possess distinctive electrical properties that make them extremely attractive in a variety of applications. Considering these, herein, we present recent advancements in bio-based dielectric polymers and nanocomposites. First, the fundamental concepts of dielectric and polymer-based dielectric materials are covered. Then, we will delve into the discussion of recent advancements in the dielectric properties and thermal stability of bio-based polymers, including polylactic acid, polyhydroxyalkanoates, polybutylene succinate, starch, cellulose, chitosan, chitins, and alginates, and their nanocomposites. Other novel bio-based dielectric polymers and their distinct dielectric characteristics have also been pointed out. In an additional section, the piezoelectric properties of these polymers and their recent biomedical applications have been highlighted and discussed thoroughly. In conclusion, this paper thoroughly discusses the recent advances in bio-based dielectric polymers and their potential to revolutionize the biomedical industry while cultivating a more sustainable and greener future.